Full-area passivating hole contact in silicon solar cells enabled by a TiOx/metal bilayer - Matsui, T; McNab, S; Bonilla, RS; Sai, H (American Chemical Society, 2022)
Passivating contacts, featuring dual functions of defect passivation at the semiconductor surface and extracting one type of charge carrier, are recognized as the key enabler in achieving high-efficiency Si solar cells. In particular, a dopant-free and full-area passivating hole contact is critical to replace the conventional rear structure that features a partial Si-metal contact design with insulator interlayers. Herein, titanium oxide (TiOx) nanolayers (∼5 nm) grown by atomic layer deposition over the full area of the Si surface followed by metal capping such as Ag are shown to provide efficient passivation and hole extraction with high optical reflectivity at the rear of Si solar cells. The proof-of-concept solar cells with either a p- or an n-Si absorber demonstrate ∼20% efficiency, exhibiting a higher infrared response compared with the conventional rear structure. Photoluminescence and electrical measurements on different TiOx/metal bilayers revealed that the field-effect passivation mechanism plays a major role in device performance, exploiting the high-concentration negative charge (>1012 q cm–2) at the Si/TiOx interface and the high work function (≥4.6 eV) of the capping metal. The developed contact offers great potential for boosting the efficiency and simplifying manufacturing of commercial Si solar cells.